The best polynomial approximation of functions analytical in the single circle - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
In the Banach space ℬ(p,q, λ), studied by M. I. Gvaradze, we establish a relation between the best polynomial approximation of an entire transcendental function and such important characteristics as its order of growth and its type.